2018
DOI: 10.1039/c7ra12525a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of high-surface-area nanoporous carbon from biomass resources and its application in supercapacitors

Abstract: High-surface-area nanoporous carbon is obtained by direct pyrolysis of biomass resources without an activation process. An electrochemical test shows high capacitance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Lately, biomass-derived CNS materials [9][10][11] attract great attention of researchers because biomass is abundant, easy-to-access and sustainable. Our earlier paper [12] reported a porous CNS with a high SSA of 1234 m 2 g -1 obtained by a simple carbonisation procedure with carefully selected carbon precursors. When these porous CNS were used as electrodes in SCs, a capacitance of 213 F g -1 can be acquired at a current density of 0.1 A g -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, biomass-derived CNS materials [9][10][11] attract great attention of researchers because biomass is abundant, easy-to-access and sustainable. Our earlier paper [12] reported a porous CNS with a high SSA of 1234 m 2 g -1 obtained by a simple carbonisation procedure with carefully selected carbon precursors. When these porous CNS were used as electrodes in SCs, a capacitance of 213 F g -1 can be acquired at a current density of 0.1 A g -1 .…”
Section: Introductionmentioning
confidence: 99%
“…These meltable inorganic salts may play a crucial activation role and improve the specific surface area of the CFSPC material. 58 Figure 3g indicates AFM topographical observations of CFSPC, further confirming the rough and uneven surface of the sheetlike carbon. The irregular sheetlike arrangement of carbon was formed with a thickness of about 2−3 nm.…”
Section: Resultsmentioning
confidence: 60%
“…It confirmed that a portion of inorganic salts (Al, Ca, K, and Mg) was found on the CFSPC material. These meltable inorganic salts may play a crucial activation role and improve the specific surface area of the CFSPC material …”
Section: Resultsmentioning
confidence: 99%
“…This indicates that NCC materials have a large number of micro- and mesoporous structures [ 23 ], which have a strong interaction with nitrogen. Meanwhile, its desorption curve overlaps with the adsorption curve without a hysteresis loop, highlighting the dominance of the microporous structure [ 24 ]. The pore size distribution was determined from their adsorption curves, and as shown, the pore size distribution peaks of the NCC samples ranged from 0 to 10 nm, confirming the microporous nature of the NCC material, which is consistent with the corresponding N 2 adsorption and desorption curves.…”
Section: Resultsmentioning
confidence: 99%